Strategies to Increase Purchase Intention of Local Brand in Indonesia: A Study of Social Media Marketing and the Role of Influencers - Susilo, Sophia Reni; Sander, Ongky Alex; Anggraini, Metta (Universitas Bunda Mulia, 2023)
Based on Hypefest and Katadata research in 2023, the growth of local brands in Indonesia is currently not matched by an optimal marketing strategy, because consumer purchase intention in local brands is still relatively low. Utilization of marketing through social media is expected to make the image of local brands more famous so as to increase consumer purchase intention, especially generations Y and Z. Optimizing marketing through social media by using influencers to introduce a product massively. The data collection technique was purposive sampling using a questionnaire, which collected 135 respondents who had never made purchases of local Indonesian brands and were active users of Instagram social media and were also generations Y and Z. The results of the study show that the first hypothesis is that there is a significant influence between social media marketing variables on consumer purchase intention. The second hypothesis is that there is a significant influence between social media marketing variables on consumer purchase intention which is moderated by the influencer variable. This proves that in the current digital era, social media is the main platform for marketing a product which will be strengthened by using the right influencers to expand the marketing of a brand. This research has limitations, namely only discussing local brands, especially in the fashion sector, so that further research can expand the local brand sector.